Ասորագիտություն եւ Ասորական եկեղեցիներ - Սեբաստիան Բրոք (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Основная цель перевода с английского труда профессора Себастиана Брока - дать нашему читателю хотя бы общее представление о сирологии и ее современных достижениях. The main aim of the translation of this work by Prof. Sebastian Brock is to give some idea to our readers on Syriac studies and its current achievements.
Keywords: History; Education